Susceptor based design strategies for enhancing microwave hybrid heating capability via experimental analysis, 3D multi-physics simulation and parametric optimization - Mohanty, A.; Patel, D.K.; Panigrahi, S.K. (International journal of thermal sciences, 2024)
Microwave processing has gained remarkable recognition based upon volumetric processing that is energy efficient. Susceptor-assisted microwave heating is a fast-emerging technology because of its advantages over traditional microwave processing. Susceptor help to speed up microwave processing by offering two-way heating with less heat loss from the material's surface. The present investigation brings out ways (theoretical, simulation and experimental) to select appropriate susceptor material by considering different types of microwaves absorbing material (alumina, yttria stabilized zirconia, boron nitride and silicon carbide) for efficient microwave heating. Theoretical analysis (dielectric properties, penetration depth, absorption loss and reflection loss) suggests silicon carbide (SiC) to be the most suitable susceptor. COMSOL Multiphysics based simulation in conjunction with experimental results were utilized for critical understanding of SiC susceptor heating. The influence of physical parameters: microwave input power, microwave frequency, placement of susceptor inside cavity and dimension of susceptor on electric field distribution and temperature profile of SiC susceptor are also investigated and presented in detail. Among all susceptor materials, SiC exhibited highest heating rate in similar operating parameters. The temperature obtained for SiC susceptor during microwave heating without casket (80 °C) was significantly lower than that with casket insulation (1003 °C). A susceptor of 10 mm thickness with cross-section of 625 mm2 was found to be the optimum dimension for SiC susceptor. The maximum temperature obtained by the SiC susceptor was 658 °C, 1003 °C, 1182 °C and 1380 °C for input power of 800 W, 1200 W, 1600 W and 2000 W respectively. Simulation data were validated with experimental results. The results exhibit a good agreement between simulation results and experimental data. •Theoretical calculations were carried out to select the best susceptor material.•Heating susceptor within casket insulation was found to be more effective.•A coupled heat and electromagnetic transfer model were considered for simulation.•The effect of frequency, power, susceptor position and dimension were discussed.•The accuracy of simulations temperature result is verified with experimental data.